Study of the impact of operation distance of outdoor portable generators under different weather conditions. Issue 8 (December 2014) - Wang, Liangzhu (Leon); Emmerich, Steven J.; Lin, Cheng-Chun
The US Centres for Disease Control and Prevention has reported that up to half of non-fatal carbon monoxide (CO) poisoning incidents during the hurricane seasons in 2004 and 2005 involved generators operated outdoors but within 7 ft of the home. Current guidance for safe operating distances of generators is often neither specific nor consistent. A study was conducted to examine the impact of generator distance on indoor CO exposure. The study was based on computer simulations of CO transport outdoors and subsequently into a generic two-storey house. This paper presents the simulation results when using an indoor air quality model coupled with a computational fluid dynamics model to predict CO concentrations near and within the home. Fire Dynamics Simulator was validated against the measured contaminant dispersion data in a wind tunnel. A parametric study was then conducted for the two-storey house to consider the effects on indoor CO levels of generator location, distance, exhaust temperature and speed and weather conditions. It was found that in most cases, to reduce CO levels for the conditions modelled, it was more effective to point the generator exhaust away from the house and position the generator at a distance of >4.6 m.